An Event Study: Efficient or Not? Share Prices' Reactions to Dividend Announcements in Hong Kong Stock Market - Leng, Xinyu (2008)
This dissertation is an event study in the area of Efficient Market Hypothesis (EMH), it focuses on exploring the impact of dividend announcements on share prices' movements in Hong Kong stock market. A sample of 43 companies containing 185 announcements within the recent 5 years is selected and t-test is employed as means to test the statistical significance of abnormal returns around the announcement dates. The result of this study suggests that the Hong Kong stock market is inefficient with regard to the semi-strong form EMH.